Social inclusion: A factor that influences the sustainable entrepreneurial behavior of generation z - Adriana Burlea-Schiopoiu; Norina Popovici (Administrative Sciences, 2024)
Young people from Generation Z are a subject of analysis for researchers because they will prevail in the labor market as successors of the Millennial generation. Taking into account the imprint that digitization has left on the behavior of Generation Z, our research aims to analyze how young people manifest their entrepreneurial intention and, mainly, how the "Me generation" perceives entrepreneurship both as a means by which they manifest their desire to control their behavior and as a factor that contributes to their social inclusion. Therefore, based on the bottom-up spillover theory, we propose to analyze the moderating effect of gender and the mediating effect of self-efficacy on the relationship between social inclusion and entrepreneurial intention. Using a quantitative research approach and a sample of 781 representatives of Generation Z, we demonstrate that social inclusion is an essential factor for Generation Z. The findings prove that Generation Z manifests a strong desire for social inclusion, which influences entrepreneurial intention, and that gender moderates this relationship. Finally, the originality of our research consists of the empirical identification of the synergy between entrepreneurial intention, self-efficacy, and the desire for social inclusion of Generation Z.
Keywords: 350; bottom-up spillover theory; entrepreneurial intention; gender; Generation Z; self-efficacy; social inclusion